Developing a conceptual framework for socioeconomic impact research in european cancer patients: a ‘best-it’ framework synthesis - Pham, Phu Duy; Schlander, Michael; Eckford, Rachel; Hernández-Villafuerte, Karla; Ubels, Jasper (The Patient, 2023)
Multiple studies have indicated a socioeconomic impact of cancer and cancer care on patients and their families. Existing instruments designed to measure this impact lack consensus in their conceptualization of the issue. Further, various terminologies have been used in the literature (e.g., financial burden, financial hardship, financial stress) without clear definitions and consistent conceptual background. Based on a targeted review of existing models addressing the socioeconomic impact of cancer, our goal was to develop a comprehensive framework from a European perspective.
Online veröffentlicht: 27. Juni 2023
Gesehen am 12.08.2024